Production of high-antioxidant yoghurt using phycocyanin from microalgae Spirulina sp - Dhyeta Ulzana Zizi Rahma; Ghiyats Hafizh Nurahman; Hadiyanto Hadiyanto; Rifqi Ahmad Baihaqi (Journal of Emerging Science and Engineering, 2023)
Yoghurt is a functional food product widely used to improve the digestive system in the body. Yoghurt fermentation usually uses lactic acid bacteria from the Lactobacillus bulgaricus, Streptococcus thermophilus, and Lactobacillus casei. Phycocyanin has been used as a natural dye for food, cosmetics, and medicine. Phycocyanin is a complex protein that can be an anticancer, antioxidant, and immunity booster. In this study, the effect of the number of additions of phycocyanin, storage time, and time of addition of phycocyanin to the antioxidant activity, protein, and organoleptic properties of the yoghurt produced. In this study, cow milk was pasteurized and fermented to become a yoghurt. Afterwards, phycocyanine was added to the yoghurt before being stored and analyzed. Spectrophotometric analysis was utilized to determine the antioxidant activity and protein content. An organoleptic test using a Likert scale was conducted to determine the product's suitability to consumer tastes. Increased phycocyanin concentrations were added (0, 0.25, 0.5, and 0.75 wt. %), resulting in a decrease in IC50 value of 8855.53, 5843.371, and 4147.548 ppm, which shows an increase in antioxidant activity. At the level of consumer preference in terms of taste, the most preferred is a concentration of 0.5 wt. %, while in terms of colour and aroma, at a concentration of 0.25 wt. %. While the longer the storage time (1, 3, and 5 days), the increase in IC50 value of 2777.111, 5179.547, and 5916.884 ppm, and there was a decrease in protein content in the sample. For the level of consumer preferences in terms of taste and aroma, the most preferred is variable with a storage time of 1 day, and in terms of colour, the most preferred at five days storage. The IC50 value in the variable with the addition of phycocyanin after fermentation is less than the addition after fermentation, which is 5351.865 ± 1606 and 3897.162 ± 1678 ppm. The protein content is higher when adding phycocyanin before fermentation. While yoghurt with the addition phycocyanin before fermentation showed higer consumer preference in terms of taste and aroma. In contrast, the addition of phycocyanin after fermentation is preferred in terms of colour.